Validity and Reliability Studies of the Indonesian Version of Arrhythmia-Specific Questionnaire in Tachycardia and Arrhythmia (ASTA) - Yamin, Muhammad; Salim, Simon; Setiati, Siti; Pudianto, Angga Pramudita; Zulmiyusrini, Putri; Tondas, Alexander Edo; Antono, Dono; Ginanjar, Eka; Mansjoer, Arif; Azizi, M Syahrir; Nachrowi, Annisa Puspitasari; Sukardi, Rubiana; et al. (Acta Medica Indonesiana, 2023)
Background: The Arrhythmia-Specific Questionnaire in Tachycardia and Arrhythmia (ASTA) was developed in Sweden using English which may pose cultural and language barriers for Indonesian patients. As such, we aimed to translate the original ASTA into Indonesian, then assess its validity and reliability. Methods: Translation of the ASTA from English to Indonesian was done using forward and backward translation. The final version was then validated with the Short Form-36 (SF-36) questionnaire. Test-retest reliability study was done in a 7-14-day interval. Results: The Indonesian version of ASTA was deemed acceptable by a panel of researchers with Cronbach’s α of 0.816 and Intraclass Correlation Coefficient (ICC) ranging from 0.856-0.983. In a comparison to the SF-36, the medication utilization domain was poorly correlated with role limitations due to physical health (r:0.384; p<0.01) and pain (r:-0.317; p<0.05). The arrhythmia-specific symptoms domain was poorly correlated with role limitations due to emotional problems (r:0.271; p<0.05). In addition, the health-related quality of life (HRQOL) domain was poorly correlated with role limitations due to physical health (r:0.359; p<0.01) and emotional problems (r:0.348; p<0.01), also total SF-36 score (r:-0.367; p<0.01). The ASTA total score was poorly correlated with role limitations due to physical health (r:0.37; p<0.01), and emotional problems (r:0.376; p<0.01), also total SF-36 score (r:-0.331; p<0.01). Conclusion: The Indonesian version of ASTA has good internal and external validity as well as good reliability. Both the physical and mental domains of ASTA are correlated with role limitations due to emotional problems and SF-36 total score.